Learning From Artemisia’s Lucretia: Embodied Suffering and Interoception in Suicide - Philippe Courtet; Philippe Courtet; Philippe Courtet; Sébastien Guillaume; Sébastien Guillaume; Sébastien Guillaume (Frontiers in Psychiatry, 2020)
In the painting “Lucretia,” Artemisia Gentileschi, one of the major painters of the 17th century, depicts Lucretia’s suicide. This artwork empathic vision offers the spectator the apprehension of a unique phenomenon where psychological pain is transformed into self-aggression. To understand why the body becomes an object to attack, it is important to study the role of interoception and self-awareness in the suicidal process. This essay discusses how bodily representations are crucial for interacting efficiently and safely with the outside world and for establishing the sense of self. It presents some of the available evidence showing that alterations in the body representation and in the sensations perceived by it contribute to suicide. Indeed, neuroimaging studies show that social environmental factors and their biological consequences in the body (e.g., increased neuroinflammation) can alter the neural networks of suicidal behavior by increasing the sensitivity to psychological pain and the disconnection from self-awareness. Therefore, body image, sensations and awareness as well as psychological pain should be examined to improve the understanding of the dynamic interactions between body, brain, and mind that underly suicidal behavior. This conceptualization brings clinical and therapeutic perspectives in a domain where they are urgently needed.